Corpus Analysis Of War Metaphor To World Health Organisation COVID-19 Press Briefing Transcripts - Muhammad Adam (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
Since Covid-19 Pandemic, World Health Organization (WHO) conducts regular press briefs to provide the development of various aspects of the pandemic. During the press brief, the use of war terms is pervasive, both in literal context and in metaphorical use. This study investigates the use of war terms metaphor in the press briefing of WHO on Covid-19 development from February 4 2020 to August 31, 2020. The aim is to identify the peak of its use and what it implied in comparison with the context of case development. Corpus analysis is conducted to seventy-eight transcripts of WHO press briefing and the data concordance is conducted using Antconc concordance software. The Conceptual Metaphor Theory of Lakoff and Johnson is used as the theoretical framework. The result shows that the peak of the war metaphor usage is in March 2020. Even though the case is increasing after March but the use of war metaphor keeps declining in the following months which suggests the shifting of the focus of communication as more has been known about the virus. Furthermore, the data shows that WHO is not only fighting the virus of Covid-19 itself, but also the infodemic and fake news at the early stage of the spread.